MOVING DIPOLE LOCALIZATION USING LINEAR LEAST SQUARE ESTIMATION: A REVIEW - DAWOD, IMAD ABDULKAREEM; SCHANZE, THOMAS; ATROSHEY, SALIH MUSTAFA S. (Journal of Duhok University, 2023)
In this review study we will shed some light on the equivalent source generators in electrocardiography and specially the moving dipole (MVD) and the characteristics of biomedical models used with this type of equivalent source generator. The mathematical derivation of the equations used in localizing this MVD is presented with the clarification of the reasons of inaccuracies due to; non-uniqueness, instability (ill-posedness) of the solution, and how a linear least square estimator method may improve the uniqueness of the solution. In addition, its experimental check in different inhomogeneity situations is also stated, the effect of blood mass on the moment and direction of the dipole throughout the ECG course is discussed too. The contribution and/or the progress of different groups of researchers in the clinical validation of MVD is concisely mentioned, furthermore some modern applications of the MVD are also presented.